Epoxidation of Eugenol from Clove Oil (Syzygium aromaticum) Using H₂O₂ Oxidizer and H₃PO₄ Catalyst - Gheje, Walburga E.; Abram, Paulus H.; Tiwow, Maria V.; Rahmawati, Sitti (Universitas Tadulako, 2025)
Clove oil (Syzygium aromaticum) contains 80–90% eugenol. Eugenol is a pale yellow liquid with several active functional groups, such as hydroxyl, aromatic rings, and allyl groups, which allow it to be modified to produce various eugenol derivative compounds. This study aims to characterize eugenol epoxy resin synthesized from clove oil eugenol using hydrogen peroxide (H₂O₂) and phosphoric acid (H₃PO₄) as a catalyst. The resulting eugenol epoxide was in the form of a yellowish-white gel with a distinctive clove aroma. It was soluble in benzene and chloroform but insoluble in ethanol. FTIR analysis showed that the epoxy compound contained an ether group (C-O-C) at absorption peaks of 1266.07 cm⁻¹ to 1018.66 cm⁻¹, a hydroxyl group (─OH) at 3347.08 cm⁻¹, a methyl group (-CH₃) at 1470 cm⁻¹ to 1350 cm⁻¹, an alkene group (C=C) at 1637.39 cm⁻¹, and a vinyl group at 910.2 cm⁻¹.